2009
DOI: 10.1007/s11250-009-9468-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of test-day records to predict first lactation 305-day milk yield using artificial neural network in Kenyan Holstein–Friesian dairy cows

Abstract: The study is focused on the capability of artificial neural networks (ANNs) to predict next month and first lactation 305-day milk yields (FLMY305) of Kenyan Holstein-Friesian (KHF) dairy cows based on a few available test days (TD) records in early lactation. The developed model was compared with multiple linear regressions (MLR). A total of 39,034 first parity TD records of KHF dairy cows collected over 102 herds were analyzed. Different ANNs were modeled and the best performing number of hidden layers and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 12 publications
2
9
0
2
Order By: Relevance
“…The maximum RMSE value belonged to MLR. Njubi et al (2010) R -pearson correlation coefficient; R 2 -coefficient of determination; σ -standard deviation; δ -the average difference between observed yields (OY) and predicted yields (PY); ρ -ratio; RMSE -root mean square error; RoM -ratio of mean.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum RMSE value belonged to MLR. Njubi et al (2010) R -pearson correlation coefficient; R 2 -coefficient of determination; σ -standard deviation; δ -the average difference between observed yields (OY) and predicted yields (PY); ρ -ratio; RMSE -root mean square error; RoM -ratio of mean.…”
Section: Resultsmentioning
confidence: 99%
“…Hosseinia et al (2007) estimated second parity milk yield and fat percentage of dairy cows based on first parity information using the neural network system. Njubi et al (2010) applied ANNs to predict first lactation 305-d milk yield using test-day records in Kenyan Holstein Friesian dairy cows. These studies have shown that total lactation yield and short-term milk yield are positively correlated (Rayalu et al, 1984;Shrivastava et al, 1988;Brutta et al, 1989;Jain et al, 1991;Jadhav et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to regression analysis, ANNs do not require prior knowledge of the problem, and the adjustment and matching between the input and output variables are performed without any assumption, thus ANNs are more suitable tools for estimation, and are more accurate than multiple linear regression, especially when models are combined in a system (Njubi, Wakhungu, & Badamana, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In developing countries, there is limited level of milk recording, and the use of test-day models would result in reduced cost of recording as we could have longer intervals between milk recording and less-frequent collection of milk samples. In this way, the amount of information that can accrue from incorporating the majority of smallholders who have small herd sizes would be large (Njubi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%